2017
DOI: 10.1159/000477349
|View full text |Cite
|
Sign up to set email alerts
|

Serum Growth Differentiation Factor 15 in Parkinson Disease

Abstract: Background: Growth differentiation factor 15 (GDF15) has been shown to be protective for dopaminergic neurons in animal and ex vivo experiments. However, little is known about its effect on the human body. Objective: This study investigated associations between serum GDF15 levels and clinical parameters in patients with Parkinson disease (PD). Methods: Idiopathic PD patients (n = 104) and age-matched controls (n = 88) were enrolled. Serum GDF15 levels were measured by human enzyme-linked immunosorbent assay. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…18 The only other report on these serum markers was undertaken in a Chinese PD cohort and only investigated GDF-15. 12 This study identified a difference in GDF-15 levels between patients with idiopathic PD and healthy controls, with a diagnostic sensitivity of 71.2%, specificity of 82.5%, and an area under the receiver operating characteristic curve of 86%. 12 This is in stark contrast to our findings, showing that GDF-15 provides no meaningful diagnostic indication.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…18 The only other report on these serum markers was undertaken in a Chinese PD cohort and only investigated GDF-15. 12 This study identified a difference in GDF-15 levels between patients with idiopathic PD and healthy controls, with a diagnostic sensitivity of 71.2%, specificity of 82.5%, and an area under the receiver operating characteristic curve of 86%. 12 This is in stark contrast to our findings, showing that GDF-15 provides no meaningful diagnostic indication.…”
Section: Discussionmentioning
confidence: 80%
“…10,11 Serum levels of GDF-15 were found to be increased in Chinese patients with PD compared with controls. 12 In contrast, GDF-15 levels in the CSF were similar in German nondemented PD patients and controls, but increased in patients with PD and dementia and patients with Lewy body dementia. GDF-15 levels were also found to correlate with age at onset of parkinsonism and age at onset of dementia, as well as with the neurodegenerative markers t-Tau and p-Tau.…”
mentioning
confidence: 87%
“…Some studies reported that higher levels of GDF-15 (plasma, serum, or cerebrospinal fluid) are associated with cognitive impairment and dementia, as well as with decreased gray matter volumes and white matter integrity. All these data suggest that GDF15 could be a possible biomarker for neurodegenerative diseases [ 70 72 ]. However, none of these studies described the levels of GDF15 for AD patients, but rather for Parkinson’s disease or Lewy Body Dementia.…”
Section: Discussionmentioning
confidence: 99%
“…As for the relationship between GDF-15 and PD, elevated levels of GDF-15 were observed in PD patients compared to age-matched controls (1,472 vs. 1,093 pg/ml, p = 0.034) in a Japanese cohort (Miyaue et al, 2020). Similarly, in Chinese Han populations, an earlier study (Yao et al, 2017) reported the difference and found that GDF-15 was an independent risk factor for the Unified PD Rating Scale-III score, further suggesting its association with disease severity. As for the participants of European ancestry, however, one recent study (Davis et al, 2020) failed to identify GDF-15 as a biomarker for PD.…”
Section: Discussionmentioning
confidence: 77%